Correlation Between Premenstrual Syndrome (PMS) and Aquatic Activities in Physical Education at High School Student Pasundan 2, Bandung City - Nur Afifah; Ahmad Hamidi; Alit Rahmat (Journal of Physical Education Health and Sport, 2025)
Abstract This study aims to explore the impact of aquatic activities on Premenstrual Syndrome (PMS) symptoms in female students at High School Pasundan 2 Bandung City. The method used in this study was a quasi-experimental with a Pretest-Posttest Control Group design, this study involved 70 female students aged 15-17 years who were divided into two groups, namely the experimental and control groups. The experimental group carried out aquatic activities for three sessions, while the control group did not receive any treatment. PMS symptoms were measured using SPAF, and aquatic activity assessments were carried out through observation sheets. The results of the paired t-test showed a significant decrease in PMS symptoms in the experimental group (p = 0.000). The independent t-test also revealed a significant difference between the experimental and control groups (p = 0.000). Most female students were in the Good to Very Good category of aquatic activities. The conclusion of this study is that aquatic activities are proven to be effective in reducing PMS symptoms and can be used as a non-medical intervention option in the context of Physical Education learning.